Anti-PD-1 Antibody Administration following Hip Fracture Surgery Reverses Immune Dysfunction and Decreases Susceptibility to Infection. (3rd April 2019) - Zhang, Hao; Chen, Chuying; He, Jiusheng; Zhang, Jianzheng; Liu, Zhi; Sun, Tiansheng
Abstract : The aim of this investigation was to assess expression of programmed death-1 (PD-1) and inflammatory status after hip fracture surgery in aged mice and to evaluate the effect of anti-PD-1 antibody intervention. Male C57BL/6 mice aged 22-28 months underwent hip fracture and femoral intramedullary pinning or a sham procedure. Expression of PD-1 was measured on CD4 + and CD8 + T cells. Additionally, the effects of anti-PD-1 antibody on lymphocyte apoptosis, cytokine production, bacterial clearance, and survival were determined. Expression of PD-1 on T cells was upregulated in mice after hip fracture and surgery compared to sham controls. Administration of anti-PD-1 antibody prevented T lymphocyte apoptosis, increased IFN- γ production in splenocytes, and decreased systemic inflammation. Antibody blockade of PD-1 significantly decreased susceptibility to bacteria and improved survival rates of aged mice after hip fracture and surgery followed by the induction of Pseudomonas aeruginosa pneumonia. This study showed that hip fracture and surgical trauma cause significant increases in PD-1 expression in aged mice. Antibody blockade of PD-1 partially reverses T cell apoptosis, decreases the systemic inflammatory response and susceptibility to bacteria, and reduces mortality.